EFFECT OF COADMINISTRATION OF URACIL OR CYTOSINE ON THE ANTITUMOR ACTIVITY OF CLINICAL DOSES OF 1-(2-TETRAHYDROFURYL)-5-FLUOROURACIL AND LEVEL OF 5-FLUOROURACIL IN RODENTS - SHIRASAKA, Tetsuhiko; IKENAKA, Kazuhiro; KITANO, Shizuo; FUJII, Setsuro (GANN Japanese Journal of Cancer Research, 1979)
Concentration of 5-fluorouracil (5-FU) in the tumor, blood, and various organs of AH130-bearing rats after administration of clinical doses of 1-(2-tetrahydrofuryl)-5-fluorouracil (FT-207) and uracil was examined. The concentration of 5-FU in blood was less than 0.02μg/ml with all combinations of FT-207 and uracil except high molar ratios of uracil to FT-207 (ratio, 5 and 10), whereas high concentrations of up to a maximum of 0.200μg/g on administration of uracil plus 5 or 7.5mg/kg of FT-207 (ratio, 4), was found in the tumor. On oral administration of FT-207 plus uracil in various combinations, the highest T/B (ratio of concentration of 5-FU in the tumor to that in blood) value was obtained at a ratio of uracil to FT-207 of 4. With this combination, 5-FU concentration in the tumor, muscle, and spleen was higher than that after administration of FT-207 alone (5mg/kg). These results suggest that at the clinical doses the optimum molar ratio of uracil to FT-207 is 4. Coadministration of cytosine enhanced the antitumor activity of FT-207 on sarcoma-180 in mice. However, cytosine enhanced the antitumor activity of FT-207 less than uracil and its coadministration resulted in a lower concentration of 5-FU in the tumor than coadministration of uracil.